The atmospheric deposition of dicarboxylic acids aerosols to the formation of the damage layers - M. Z. H. Rozaini (2021)
Study of the morphology of calcium carbonate with the presence of Dicarboxylic Acids (DCA’s) aerosol has been carried out. The experiments show that oxalic acid readily converts calcium carbonate to calcium oxalate and malonate. However, the higher molecular weight of DCA’s tend not to lead to calcium dicarboxylate quite so readily. Calcium succinate and calcium adipate were observed, but more significantly succinic, adipic and glutaric acids seem to block some of calcium carbonate sites in the lattice and inhibit crystal formation. These higher molecular weight DCA’s appear to encourage the transformation among the three polymorphs of calcium carbonate: calcite, aragonite and vaterite. Vaterite was especially evident in the case of adipic and glutaric acids. The presence of vaterite may be a clue to the activities of the higher DCA’s. The conversion of calcium carbonate to calcium dicarboxylate by the presence of DCA’s can be considered as the morphology transformation of the carbonatic stone from the crystallization-dissolution in the porous matrix of the DCA’s, that lead to mechanical stresses and chemical alterations that can damage monuments and historical buildings.